1989
DOI: 10.1002/jmv.1890280403
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of hepatitis b virus, hepatitis d virus, and human immunodeficiency virus infections among parenteral drug abusers in southern taiwan

Abstract: A total of 390 parenteral drug abusers (PDAs) at the Kaohsiung Municipal Narcotics Abstention Institute were examined for markers of hepatitis B virus (HBV), hepatitis D virus (HDV), and human immunodeficiency virus (HIV). All sera were tested for hepatitis B surface antigen (HBsAg), surface antibody (anti-HBs), and core antibody (anti-HBc) by radioimmunoassay (RIA) and for antibody to HIV (anti-HIV) by enzyme-linked immunosorbent assay (ELISA). Hepatitis B e antigen (HBeAg) and antibody to HDV (anti-HDV) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In multivariate logistic regression, we also confirmed that tattoo was an independent related factor for being anti‐HCV positive. Several studies also have reported this consistent evidence of the link between tattoo and HCV infection in Taiwan 30–32 . In this study’s subjects the typical process of tattooing was done in the general community before entering prison.…”
Section: Discussionsupporting
confidence: 74%
“…In multivariate logistic regression, we also confirmed that tattoo was an independent related factor for being anti‐HCV positive. Several studies also have reported this consistent evidence of the link between tattoo and HCV infection in Taiwan 30–32 . In this study’s subjects the typical process of tattooing was done in the general community before entering prison.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to the i.v. drug users in the Western countries, those in Taiwan are not yet affected by HIV as evidenced by seronegativity of HIV in this population [Beasley et al, 1981;Chung et al, 1989]. The prevalence of HCV infection among drug users has decreased significantly from 53% in our previous study in 1985 to 41% in the current study, with an estimated decrement rate of 0.75%/year [Lee et al, 1991].…”
Section: Discussionmentioning
confidence: 50%
“…By contrast, throughout China, Japan, and Southeast Asia, anti-HD seroprevalence is very low except for several isolated groups (43,44,50,102,134,162,163,196,206). High levels of HDV infection have been found in intravenous drug users in Taiwan (84%) (43,49) and in approximately 20% of Taiwanase prostitutes (87). In contrast to studies showing low prevalence of HDV infection in Southeast Asia and China, studies of over 2,300 HBsAg-positive subjects from six countries and nine islands in the Western Pacific revealed foci of high anti-HD seroprevalence in the islands of Western Samoa, Niue, Nauru (60), and the Pacific Republic of Kiribati (202).…”
Section: Virus-encoded Proteinsmentioning
confidence: 99%